PENGGUNAAN MODEL WORD SQUARE DALAM PENINGKATAN PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA KELAS IV SD - Yulianti, Rusmidah (KALAM CENDEKIA PGSD KEBUMEN, 2013)
Abstract. The Using of Word Square Model for Increasing English Vocabulary in the Fourth Grade Students State Elementary School. The purpose of this research to increase English vocabulary for the fourth grade students using Word Square model. This research is a class action research in three cycle. The subjects were elementary school students in fourth grade state Mangunranan with total 24 students. Data collection techniques using observation, interviews, tests, analysis of students work, and questionnaires. Data analysis using qualitative analysis data technique. The validation of data is using triangulation technique. The conclusions show the Word Square model can increase English vocabulary for the fourth grade students state elementary school. Keywords: Word Square, Vocabulary, English Abstrak. Penggunaan Model Word Square dalam Peningkatan Penguasaan Kosakata Bahasa Inggris Siswa Kelas IV SD. Tujuan penelitian meningkatkan penguasaan kosakata bahasa Inggris siswa kelas IV menggunakan model Word Square. Penelitian ini penelitian tindakan kelas dalam tiga siklus. Subjek penelitian siswa kelas IV SDN Mangunranan semester 2 sejumlah 24 siswa. Teknik pengumpulan datanya observasi, wawancara, analisis kerja murid, tes, dan angket. Analisis data menggunakan analisis data kualitatif. Validitas data menggunakan teknik triangulasi. Hasil penelitian menunjukan penggunaan model Word Square dapat meningkatkan penguasaan kosakata bahasa Inggris siswa kelas IV SD. Kata Kunci: Word Square, Kosakata, Bahasa Inggris